Relasi Antara Guru dan Siswa: Sebuah Tinjauan dari Sudut Pandang Alkitabiah [The Relationship Between Teachers and Students: A Biblical Review] - Pitaya Rahmadi; Chusmiaty Rombean (Diligentia: Journal of Theology and Christian Education, 2021)
Humans are social creatures who are inseparable from interactions or relationships with each other. This interaction can occur because of communication. It contributes to realizing the Cultural Mandate, the Great Commandment, and the Great Commission from God. Communication has a significant role in education, especially in the learning because communication can help to achieve learning goals in education. However, in the learning process communication between teachers and students does not always work effectively, this fact impedes achieving educational goals. One of reasons is teachers and students do not understand the basis of communication and their nature as teachers and students. Therefore, this paper aims to discuss more deeply about the basis of communication in building relationships between teachers and students viewed from biblical perspectives as a guide to true truth. Basically, communication created by God for His glory. A teacher is there to guide students to the path of wisdom for knowing Jesus Christ especially through Christian education. Students need to be guided because students are individuals who have sin but also have their own potential and uniqueness. Therefore, through effective communication, this issue can be achieved. Communication that builds relationships occurs when based on the principle of Christianity by respecting the image and likeness of God that is in our communicant.